The Effect Of Financial Information On Firm Value With Csr Disclosure As A Moderating Variable In The Energy Sector On The Indonesia Stock Exchange 2021-2024 Period - Ayu Rachmawati; Etty Puji Lestari; Faizul Mubarok (UNIVED Press, 2026)
This study aims to analyze the effects of profitability, firm size, and leverage on firm value, as well as to examine the moderating role of CSR disclosure in energy sector companies listed on the Indonesia Stock Exchange during 2021–2024. This research employs a quantitative approach with a causal research design. Secondary data were obtained from financial statements and sustainability reports of energy sector companies. Data collection was conducted using documentation techniques with purposive sampling, resulting in 23 sample companies. Panel data regression with moderation analysis was applied using EViews 13 software. The results indicate that profitability and firm size have no significant effect on firm value, while leverage has a significant positive effect. CSR disclosure has a significant positive effect on firm value. Furthermore, CSR disclosure does not moderate the relationship between profitability and firm value nor between firm size and firm value, but it significantly weakens the positive effect of leverage on firm value in energy sector companies. These findings suggest that firm value in the energy sector is influenced not only by financial performance but also by sustainability considerations. Therefore, companies are encouraged to integrate financial strategies and CSR disclosure, while investors should consider both financial and nonfinancial information.